An automated multi-point primary vibration calibration system. (December 2021) - Kokuyama, Wataru; Shimoda, Tomofumi; Nozato, Hideaki
Abstract: In this study, we developed an automated, multi-point primary vibration calibration system using a two-axis positioning stage and a laser Doppler vibrometer. The proposed system offers low-cost, convenient, and automated multi-point vibration calibration, enabling less calibration lead time. The positioning stage also offers a better positioning repeatability of 1 μm, which is impossible to achieve through manual alignments. We successfully measured the surface deformation of a laser reflection adaptor for a single-ended vibration pickup at 18.5 kHz. Visualizing the deformation of laser reflection surfaces facilitates the understanding of the effects of deformation or nonrectilinear motion, which are among the largest uncertainty components in high-frequency vibration calibrations.